Development of a Consensus-based Agenda to Identify Priorities for Clinical Research in Pediatric Orthopaedic Surgery - A. Noelle Larson, MD; Ria Paradkar; Matthew Schmitz, MD; Raymond Liu, MD; Neeraj M. Patel, MD, MPH, MBS; Henry Ellis, MD; Todd A. Milbrandt, MD; Dan Sucato, MD; Kevin Shea, MD; Jennifer Laine, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: There is a need for additional high quality studies in children’s orthopaedic surgery to answer important clinical research questions. The purpose of this study was to develop a consensus-based research agenda to identify top clinical questions to prioritize in pediatric orthopaedics. Methods: A modified Delphi technique was used, where the membership of the Pediatric Orthopaedic Society of North America (POSNA) was asked to submit clinical research questions and then queried iteratively to gain consensus. A steering committee from the POSNA leadership members was assembled to administer, consolidate, and edit survey responses. Final scores were used to select the top 16 research questions distributed by subspecialty area. Results: Based on the call for clinical research questions, 78 orthopaedic surgeons and scientists submitted 116 research questions. The steering committee removed duplicate questions and harmonized submissions to 65 clinical research questions. In spring 2024, the POSNA membership participated in stage 1 voting and submitted 33 additional questions. Duplicate questions were removed. The final voting round included 108 surgeons who rated 54 questions from low (1) to high priority (5). The top scoring questions from each subspecialty area were selected to comprise the POSNA consensus-based clinical research agenda. The top scoring questions were related to the role of orthopaedic surgical treatment in cerebral palsy and surgical indications for residual hip dysplasia. Conclusions: This consensus-based research agenda may guide surgeons, researchers, study group consortia, and funding organizations to improve the clinical evidence in children’s orthopaedic surgery and promote high-quality prospective studies. Key Concepts: (1) Despite the significant burden and cost of pediatric musculoskeletal conditions, pediatric orthopaedic research receives low research funding, underscoring the need for a focused research agenda. (2) This study used a modified Delphi process to engage pediatric orthopaedic surgeons across multiple pediatric orthopaedic subspecialties in the development of a consensus-based research agenda in order to identify high-priority clinical questions. (3) The final agenda reflects critical gaps in pediatric orthopaedic care, including conditions that impact long-term function and quality of life in pediatric orthopaedic patients. (4) The final agenda aims to guide future research, foster multicenter collaboration, and advocate optimized allocation of funding to improve evidence-based pediatric orthopaedic care. Level of Evidence: Level IV (consensus-based expert opinion study)